ÉLABORATION DE SUPPORTS POREUX CARBONÉS PAR IMPRÉGNATION - Hanane BELAYACHI (My University, 2016)
This thesis falls within the general framework of the treatment of wastewater by conventional and emerging processes. Three nano-materials were utilized to develop the aim of this work. The three materials were characterized by SEM, BET, XRD and FTIR techniques. The grape marc considered as a vegetal waste was valorized thermochemically to be used for the adsorption of two azo dyes in aqueous solution. The titanium oxide in its anatase phase was used to degrade the same dyes. To reconcile the two processes, treatment of these molecules was performed in the presence of a hybrid material synthesized by impregnating (coating) the activated carbon by TiO2-anatase. Both molecules AO7 and RB5 dyes were make in reactions in the presence of the three materials to verify their adsorptive and photocatalytic properties. The valorized materials and synthesized one have showed significant adsorption and heterogeneous photocatalysis capacities. This offers a great advantage for wastewater treatment since the hybrid material regenerates itself after contact with the pollutant. This feature applies only in the presence of a low cost energy source to guarantee the perpetuity of activated carbon.